Rambo - Stallone, Sylvester; Benz, Julie, 1972-; Schulze, Paul.; Marsden, Matthew, 1972-; McTavish, Graham; Gallegos, Rey.; Kang, Tim, 1973-; La Botz, Jake.; Khin, Maung Maung; Howard, Ken, 1944-2016 (Santa Monica, Calif. : Lionsgate, 2008)
Vietnam veteran John Rambo has withdrawn into a simple and secluded existence in Thailand. Even though he is looking to avoid trouble, trouble finds him. A group of Christian missionaries approach Rambo with the desire to rent his boat to travel up the river to Burma, which is a war zone. The Karen people of the region have endured a brutal rule from the murderous Burmese military. Rambo accepts the offer and takes the missionaries up the river. When the missionaries finally arrive at the Karen village, they find themselves part of a raid led by the sadistic Major Pa Tee Tint and his command. Some of the villagers and missionaries are murdered. The rest are held as captives. Concerned by their disappearance, the minister in charge of the mission gathers a group of mercenaries. Rambo, who knows the exact dropoff, transport them with his boat. Rambo joins the team and helps liberate the survivors in what may be one of his deadliest missions ever.
Originally released as a motion picture in 2008.
Presented in widescreen format.
Director of photography, Glen MacPherson ; editor, Sean Albertson ; music, Brian Tyler ; costume designer, Lizz Wolf ; production designer, Franco-Giacomo Carbone.
Sylvester Stallone, Julie Benz, Paul Schulze, Matthew Marsden, Graham McTavish, Rey Gallegos, Tim Kang, Jake La Botz, Maung Maung Khin, Ken Howard.
MPAA rating: R.
DVD, region 1, widescreen (2.35:1) presentation; Dolby Digital 5.1 surround.
Keywords: Rambo, John J. (Fictitious character) -- Drama; Missionaries -- Burma -- Drama; Karen (Southeast Asian people) -- Burma -- Drama; Murder -- Burma -- Drama; Action and adventure films; Thrillers (Motion pictures, television, etc.); Video recordings for the hearing impaired; Feature films